Nuclear paraspeckle assembly transcript 1 promotes the podocyte injury via targeting miR-23b-3p/B-cell lymphoma-2 interacting protein 3 like axis. Issue 1 (31st December 2022) - Wang, Jing; Luo, Junpeng; Du, Li; Shu, Xin; Guo, Chengyu; Li, Tanshi
Abstract: Background: Given the reported effects of nuclear paraspeckle assembly transcript 1 (NEAT1) on kidney injury, a study is worth formulating to investigate whether and how NEAT1 impacts podocytes. Materials and methods: A mouse podocyte injury model was established using the adriamycin (ADR)-induced mouse podocyte cell line (MPC5). The target relationships between NEAT1 and microRNA (miR)-23b-3p and between miR-23b-3p and Bcl-2 interacting protein 3 like (BNIP3L) were verified by dual-luciferase reporter assay and RNA immunoprecipitation assay. After ADR-induced MPC5 cells were transfected with NEAT1 overexpression plasmid (oe-NEAT1) or shNEAT1, the viability and apoptosis of MPC5 cells were evaluated by Cell Counting Kit-8 (CCK-8) assay and flow cytometry, respectively. The expressions of MPC5, miR-23b-3p, BNIP3L and the factors related to podocyte injury, apoptosis and epithelial-mesenchymal transition were determined using quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot. Results: NEAT1 was high-expressed in ADR-induced cell model. After transfection with oe-NEAT1, the expression of NEAT1, the levels of marker (Desmin) and apoptosis were promoted, while the viability and the levels of podocyte injury markers (WT1, Nephrin) were inhibited in ADR-induced cells. However, shNEAT1 generated the effects opposite to oe-NEAT1. Besides, miR-23b-3p competitively bound to NEAT1 and targeted BNIP3L. MiR-23b-3p inhibitor reversed the effect of shNEAT1, while its effect could be further offset by shBNIP3L. Furthermore, miR-23b-3p inhibitor affected mouse podocyte injury through downregulating Bcl-2 and E-cadherin levels and upregulating Cleaved-caspase-3, Bax, N-cadherin, Vimentin and Snail levels, but shBNIP3L did oppositely. Conclusion: NEAT1 promotes the podocyte injury via targeting miR-23b-3p/BNIP3L axis.